2017
DOI: 10.17081/psico.21.39.2827
|View full text |Cite
|
Sign up to set email alerts
|

Vivir con VIH: experiencias de estigma sentido en personas con VIH

Abstract: ResumenObjetivo: Reconocer los significados colectivos y subjetivos que un grupo de personas con VIH tiene respecto a vivir con la enfermedad.Método: Cualitativo explicativo con diseño narrativo. Los datos fueron recolectados a través de tres grupos de discusión conformados por 16 personas con VIH, hombres y mujeres entre los 22 y los 49 años de edad, que viven en la ciudad de Cali.Resultados: Los significados de los participantes giran en torno al vivir el VIH, en relación con el estigma sentido, el estigma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 9 publications
0
7
0
13
Order By: Relevance
“…A stigma is a degrading social assessment or label that is attached to those who show undesirable social features. Stigmatization is the social process by which degrading social assessments or labels and the consequent emotional or behavioral responses are generated and maintained, thus causing and shaping social exclusion (Elizondo et al, 2015;Guevara-Sotelo & Hoyos-Hernández, 2018;Varas-Díaz et al, 2008;Varas-Díaz & Neilands, 2009;Rivas et al, 2009;Rosa & Varas, 2008). Different studies have revealed that people with HIV are one of the most stigmatized collective groups in the world.…”
Section: Social Stigma Of Hiv/aidsmentioning
confidence: 99%
See 4 more Smart Citations
“…A stigma is a degrading social assessment or label that is attached to those who show undesirable social features. Stigmatization is the social process by which degrading social assessments or labels and the consequent emotional or behavioral responses are generated and maintained, thus causing and shaping social exclusion (Elizondo et al, 2015;Guevara-Sotelo & Hoyos-Hernández, 2018;Varas-Díaz et al, 2008;Varas-Díaz & Neilands, 2009;Rivas et al, 2009;Rosa & Varas, 2008). Different studies have revealed that people with HIV are one of the most stigmatized collective groups in the world.…”
Section: Social Stigma Of Hiv/aidsmentioning
confidence: 99%
“…Different studies have revealed that people with HIV are one of the most stigmatized collective groups in the world. The perception of seriousness of the infection, along with wrong beliefs about its transmission through casual or social contact and the ability of controlling the stigma (blaming people with HIV) influence the detrimental attitudes (Elizondo et al, 2015;Guevara-Sotelo & Hoyos-Hernández, 2018;Varas-Díaz et al, 2008;Varas-Díaz & Neilands, 2009;Varas-Díaz et al, 2017;Wodajo et al, 2017;Rosa & Varas, 2008;Fuster-Ruiz et al, 2016).…”
Section: Social Stigma Of Hiv/aidsmentioning
confidence: 99%
See 3 more Smart Citations